Analysis of the Use of Artificial Intelligence (AI) in Human Resources Management (HR): Study at PT Semen Baturaja Persero (SMBR) - Bakar, Abu; Syah Amin Albadry; Silvia Jessika; Syahwami; Joko Sunaryo (Enigma Institute, 2024)
The use of artificial intelligence (AI) in human resource management (HR) has grown rapidly in recent years. AI has the potential to improve the efficiency, effectiveness and accuracy of HR processes. PT Semen Baturaja Persero (SMBR) is one of the largest cement companies in Indonesia. SMBR has applied AI to various HR processes, including recruitment and selection, training and development, performance appraisal, and compensation and benefits. This research aims to analyze the use of AI in HR management at SMBR. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with stakeholders in SMBR. The research results show that AI has provided significant benefits for SMBR in HR management. AI has helped SMBR to improve the efficiency of HR processes, such as recruitment and selection, training and development, and performance appraisal; improving the effectiveness of HR processes, such as recruitment and selection, and performance appraisal; improve the accuracy of HR processes, such as recruitment and selection, and performance appraisal. AI has great potential to improve HR management in SMBR.